L'ordoliberalismo e la ricerca della sacralità - Josef Hien (Biblioteca della libertà, 2016)
Ordoliberalism has been identified as an important ideational force during the European sovereign debt crisis. A vivid scholarly and public debate has erupted on how much influence the ideology had on the German position during the crisis. This article concentrates on an aspect that this debate has so far omitted: the cultural foundations and the ethical provisions of Ordoliberalism. The article explores the genealogy of Ordoliberal thinking and shows that it has profound roots in German Protestant social teachings. The religious connection ensured the political survival of Ordoliberalism in the highly religious environment of post-WWII Germany. With the decline of organized religion form the 1960s onwards, Ordoliberalism adopted the myth of the social market economy as a civil religion to ensure the ideology's survival.
Keywords: 330